Research progress on the synthesis process, detection method, pharmacological effects and application of glycocholic acid - Li, Jiahui; Zhang, Chungang; Wang, Yang; Tian, Minyuan; Xie, Chao; Hu, Heng (Frontiers in Pharmacology, 2025)
ObjectiveThis review aims to summarize the research progress of glycocholic acid to promote its broader development and application.MethodsThis article collects relevant literature from databases such as Science Direct, PubMed, Web of Science, Google Scholar and CNKI from the establishment to 2024, systematically organizing and analyzing aspects of glycocholic acid including its physicochemical properties, synthesis and extraction techniques, detection methods, pharmacological effects, mechanisms of action, clinical research, and application as an excipient.ResultsGlycocholic acid, as a key conjugated component in bile acids, exhibits various pharmacological effects such as anti-inflammatory and antioxidant activities. Nevertheless, current research on glycocholic acid is insufficient, with synthesis techniques requiring improvement, limited application of detection technologies, and a need for in-depth exploration of its pharmacological mechanisms. Due to its amphiphilic molecular structure, glycocholic acid is primarily used as a pharmaceutical excipient.ConclusionThis review summarizes the existing research on glycocholic acid, indicating that future research should strengthen work in this field, including improving synthesis processes and enhancing the sensitivity of detection technologies, to provide a scientific basis for the development of new formulations and drug combinations, thereby promoting the advancement of traditional Chinese medicine.